The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00415-010-5479-6
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime prevalence and incidence of parasomnias in a population of young adult Nigerians

Abstract: Lifetime prevalence, incidence, and risk factors for parasomnias were determined. Past experiences of non-REM, REM, and sleep-transition parasomnias were recorded. Diaries of night sleep duration, parasomnias, perception of aliens, levels of physical activity, headaches and intake of all substances, drugs, and tobacco were kept for 14 consecutive days. A total of 276 subjects were studied. Lifetime prevalences (95% CI) were 725 (668-776) for occurrence of any parasomnia, 43 (25-74) for sleepwalking, 112 (80-15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
0
18
2
1
Order By: Relevance
“…Multiracial studies in USA also observed that parasomnias are more common among African-Americans compared to Caucasians and that traumatic events were associated with an increased frequency of parasomnias in the population [36,37] In this study, the prevalence of parasomnias in PWE was 46% which was consistent with the findings from the previous studies. [4,5] The prevalence of parasomnias in this study is higher than that reported by Busulli et al, [37] who observed that 34% of patients with nocturnal frontal lobe epilepsy had NREM parasomnias and that of Manni et al, [38] with a prevalence of 10% for REM sleep behavior disorder in elderly subjects with epilepsy.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…Multiracial studies in USA also observed that parasomnias are more common among African-Americans compared to Caucasians and that traumatic events were associated with an increased frequency of parasomnias in the population [36,37] In this study, the prevalence of parasomnias in PWE was 46% which was consistent with the findings from the previous studies. [4,5] The prevalence of parasomnias in this study is higher than that reported by Busulli et al, [37] who observed that 34% of patients with nocturnal frontal lobe epilepsy had NREM parasomnias and that of Manni et al, [38] with a prevalence of 10% for REM sleep behavior disorder in elderly subjects with epilepsy.…”
Section: Discussioncontrasting
confidence: 81%
“…In the previous study carried out by Oluwole [4] among medical student's, increased duration of sleep and alcohol intake were associated with parasomnias, while smoking, intake of caffeinated drink and male gender were not associated with parasomnias. Though there is a paucity of literature on the risk factors that were predictive of the presence of parasomnias in PWE however in this study, none of the sociodemographic or epilepsy-related variables predicted the occurrence of parasomnias in the PWE, the reasons for this finding are unclear but might probably be due to possibility of differences in risk factors that could predispose the general population and PWE to development of parasomnias.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A prevalence of 19.2% was calculated in the same group after a follow‐up period of 5 years when the mean age had reached 13.7 . In contrast to insomnia, parasomnia decreases as children get older . Furet et al .…”
Section: Discussionmentioning
confidence: 99%